Efficiency of the Sensory Mapping Score for Hansens’s disease diagnosis and follow-up: a functional cure criterion? - Frade, Marco Andrey Cipriani; Albertino, Gustavo Sartori; Sabino, João Vitor da Silva; Lima, Filipe Rocha (Frontiers in Medicine, 2025)
IntroductionCurrent operational criteria for Hansen’s disease (HD), which are primarily based on lesion count and fixed-duration multidrug therapy, tend to overlook the neurological spectrum of the disease and fail to define cure in terms of functional recovery. The objective was to develop and validate a Sensitive Mapping Score using Semmes-Weinstein Monofilaments to assess and monitor cutaneous sensory impairment in HD lesions during treatment with the RIMOXCLAMIN regimen.MethodsA prospective cohort of 40 patients was followed over a 12-month period. Tactile sensitivity was evaluated in the hands, feet, and cutaneous lesions at 3-month intervals using a standardized SWM mapping system. Color-coded responses were converted into a numerical score reflecting the degree of sensory impairment. Clinical, neurological, and laboratory parameters were assessed in parallel.ResultsAlthough only 32.5% of patients met the multibacillary classification based on lesion count, 100% exhibited altered tactile sensation and 80% presented with nerve thickening. The SMS demonstrated early sensitivity to neurological improvement, with significant changes observed by the third month (p = 0.0156). By 12 months, 74.3% of lesions had achieved complete sensory recovery. The progression of SMS scores paralleled reductions in pain levels, nerve palpation abnormalities, and physical disability grades. No linear correlation was found with standard hand and feet scores, reinforcing the SMS’s complementary value in capturing localized sensory recovery.ConclusionThe SMS is a low-cost, accessible, and objective tool for neurological monitoring in HD. It quantifies functional recovery in cutaneous lesions, offering a clinically meaningful alternative to the concept of an “administrative cure.” Its adoption could guide individualized treatment durations, enhance therapeutic decision-making, and promote a shift toward function-based definitions of cure in HD management.